2009
DOI: 10.1038/ejhg.2009.37
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and molecular modelling of novel MPZ mutations in demyelinating and axonal neuropathies

Abstract: Mutations in the myelin protein zero (MPZ) gene have been associated with different Charcot-MarieTooth disease (CMT) phenotypes, including classical demyelinating CMT1B and the axonal form of the disease (CMT2). The MPZ role in the pathogenesis of both demyelinating and axonal inherited neuropathies was evaluated in the Italian population by screening a cohort of 214 patients with CMT1 or CMT2. A MPZ mutation frequency of 7.9% in demyelinating cases and of 4.8% in axonal cases was observed. In the total cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…Protein misfolding and aggregation caused by genetic mutations or other factors has been shown to underlie the pathogenesis of many neurological diseases, including Parkinson disease and Alzheimer disease (Selkoe, 2004). Our findings that CMT1C mutations cause SIMPLE protein misfolding and aggregation, together with previous reports linking misfolded peripheral myelin protein 22 (PMP22) and myelin protein zero (MPZ) to other subtypes of demyelinating CMT (Shames et al, 2003;Myers et al, 2008;Mandich et al, 2009), suggest protein misfolding as a common cause of demyelinating peripheral neuropathies.…”
Section: Discussionsupporting
confidence: 47%
“…Protein misfolding and aggregation caused by genetic mutations or other factors has been shown to underlie the pathogenesis of many neurological diseases, including Parkinson disease and Alzheimer disease (Selkoe, 2004). Our findings that CMT1C mutations cause SIMPLE protein misfolding and aggregation, together with previous reports linking misfolded peripheral myelin protein 22 (PMP22) and myelin protein zero (MPZ) to other subtypes of demyelinating CMT (Shames et al, 2003;Myers et al, 2008;Mandich et al, 2009), suggest protein misfolding as a common cause of demyelinating peripheral neuropathies.…”
Section: Discussionsupporting
confidence: 47%
“…The MPZ mutation can cause demyelinating CMT (CMT1B), axonal CMT (CMT2I/2J), Dejerine‐Sottas neuropathy, or congenital hypomyelinating neuropathy (Dacci et al ., ) . Currently, more than 120 different MPZ mutations, both familial and sporadic, have been described (http://www.molgen.ua.ac.be/CMTMutations) (Mandich et al ., ) .…”
Section: Discussionmentioning
confidence: 97%
“…[6][7][8] and MPZ. 9,10 How misfolding of these membrane proteins with different topologies contributes to demyelinating neuropathy remain unknown. We found that misfolded SIMPLE forms abnormal cytosolic aggregates and mediates erroneous interactions with cellular proteins, 3 which are pathogenic mechanisms characteristic of many protein-misfolding diseases.…”
Section: P Eripheral Neuropathies Such As Charcot-mentioning
confidence: 99%